1992
DOI: 10.5014/ajot.46.5.434
|View full text |Cite
|
Sign up to set email alerts
|

The Americans With Disabilities Act of 1990 and Employees With Mental Impairments: Personal Efficacy and the Environment

Abstract: The Americans With Disabilities Act of 1990 (ADA) (Public Law 101-336) provides persons with mental health problems basic rights resulting in full access to community resources, especially the rights and privileges associated with the work role. This paper discusses the law, personal self-efficacy, and four environmental aspects as they relate to the employment of persons with mental impairments: (a) employer and co-worker attitudes, (b) essential job functions, (c) reasonable accommodations, and (d) community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…In general, client factors such as diagnosis, symptoms, age, gender and ethnicity have not been strong or consistent predictors of vocational success . Several authors have documented information about the nature and type of supports that are important for individuals with a mental illness (Crist & Stoffel, 1992;Marrone, Balzell, & Gold, 1995;Parent, Unger, Gibson, & Clements, 1994). For those who do find competitive work, Becker, Drake et al (1998) found that events during the job placement often occurred which led to unsatisfactory job terminations.…”
Section: © Caot Publications Acementioning
confidence: 99%
See 1 more Smart Citation
“…In general, client factors such as diagnosis, symptoms, age, gender and ethnicity have not been strong or consistent predictors of vocational success . Several authors have documented information about the nature and type of supports that are important for individuals with a mental illness (Crist & Stoffel, 1992;Marrone, Balzell, & Gold, 1995;Parent, Unger, Gibson, & Clements, 1994). For those who do find competitive work, Becker, Drake et al (1998) found that events during the job placement often occurred which led to unsatisfactory job terminations.…”
Section: © Caot Publications Acementioning
confidence: 99%
“…Crist and Stoffel (1992) highlight ways in which occupational therapists can negotiate reasonable accommodations with employers. Rather than our traditional focus on assessment and skill development, we need to shift our focus, at least initially, to developing and accessing supports in the work environment.…”
Section: Implications For Occupational Therapymentioning
confidence: 99%
“…Although it is difficult to list all job functions, the most prevalent performance skills required for a job must be written. Unwritten assumptions about job requirements no longer apply (Crist & Stoffel, 1992). To further illustrate this point, Crist & Stoffel (1992), described a case study of an occupational therapist with an emotional disability who was dismissed because she didn't model appropriate behaviour for the patients.…”
Section: Americans With Disabilities Act (Ada)mentioning
confidence: 99%
“…Unwritten assumptions about job requirements no longer apply (Crist & Stoffel, 1992). To further illustrate this point, Crist & Stoffel (1992), described a case study of an occupational therapist with an emotional disability who was dismissed because she didn't model appropriate behaviour for the patients. The occupational therapist was able to sue the hospital on the grounds that she was dismissed for not being able to perform a marginal job requirement.…”
Section: Americans With Disabilities Act (Ada)mentioning
confidence: 99%
See 1 more Smart Citation